Análisis de las estrategias de comunicación institucional que utiliza el gobierno autónomo descentralizado municipal de Loja en las parroquias urbanas para la difusión de las obras públicas realizadas en el cantón Loja, durante el periodo marzo- diciembre 2015 - Gonzalez Ruiz, Karina Mariuxi (2016)
Analyze Institutional Communication Strategies that the Government Decentralized Autonomous Municipal de Loja used in urban parishes for the dissemination of public works in the canton Loja, during the period March-December 2015, subject and general objective to investigate, before it is believed appropriate use of methods: scientific, deductive, analytical, statistical, synthetic and descriptive, which were vital during the research process. They also enabled to determine the causes and effects of the problem, concluding that institutional communication strategies used by the Municipality of Loja, are not adequate, giving the dissemination running the department of corporate communication of Municipal GAD Loja is manipulated extemporaneously because of the lack of a strategic communication plan for the dissemination of public works. This was evident through surveys and interviews based on the opinion of the citizens and officials of the Municipality, the Department of institutional communication has tried to solve the problem through a media plan for the dissemination of public works, but this is not enough to cover with the target audience or target by escaza use of media in the province of Loja, being of vital importance that the competent authorities of the department of corporate communication of the Municipality of Loja, develop a strategic communication plan in order to provide wider dissemination of information to the public.